Resilience, Cardiological Outcome, and Their Correlations With Anxious-Depressive Symptoms and Quality of Life in Patients With an Implantable Cardioverter Defibrillator - Isella, Celeste; Gasparini, Alessandra; Lucca, Giulia; Ielmini, Marta; Caselli, Ivano; Poloni, Nicola; Dajelli Ermolli, Carlo; Caravati, Fabrizio; Castiglioni, Battistina; De Ponti, Roberto; Callegari, Camilla (Frontiers in Psychiatry, 2021)
Background. Resilience is proven as a protective factor against the development of psychiatric disorders and it has gained clinical relevance in development and progression of cardiovascular pathology. The authors performed a longitudinal study on patients with Implantable Cardioverter Defibrillator (ICD) with the primary aim to highlight the possible existence of a correlation between individual resilience capacity, depressive and anxiety symptoms, and quality of life in terms of outcomes. Secondary aim was to analyze the differences between patients with major cardiac events in the follow up and patients without cardiac events with respect to the previous variables. Materials and methods. 80 patients enrolled in the Cardiology Unit were evaluated at T0 and during the follow up through the following scales: the 14-item Resilience Scale (RS-14), the Hospital Anxiety and Depression Scale (HADS), the World Health Organization Quality of Life-Brief Version (WHOQOL-Bref). Results. A significant linear correlation between resilience and all the areas of quality of life at T0, T1, and T2 emerged. A negative correlation between resilience, and anxiety and depressive symptoms emerged, and between depression, and anxiety and quality of life. Patients with cardiac events during the follow up have shown a worse quality of life and the onset of anxiety-depressive symptom over time, without changes of the resilience scores. Patients without cardiac events showed an increasing trend in resilience scores. Discussion. Given the speed and simplicity of use of the RS-14 scale, it seems promising to further investigate the clinical usefulness of this instrument also in the cardiology field.